The Effectiveness of Cinema Therapy in Increasing Empathy in Students of English Education Study Program - Risna Mardiah Mardiah; Isnaini Ma'rifah (Journal of Psychology and Social Sciences, 2024)
Empathy is a form of attention that involves emotional connection to understand the feelings of others. However, many adolescents are unable to explore their empathy so there needs to be an effort to increase it. On way that can be done to increase empathy is by using cinema theraoy techniques. Cinema therapy is a counseling method using films to have a positive effect on the counselee. In this film, treatments that contain empathy values are used. The purpose of this study is to analyze the effectiveness in increasing empathy in students. This study uses a quantitative approach with a pre-experimental design method of one-group pre-test post-test type to see the effect of cinema therapy in increasing empathy. Respondents in this study involved 15 tarbiyah students of English study program class of 2021 UIN Raden Fatah. The data obtained through the empathy scale was then analyzed with the help of SPSS version 20. The results of this study indicate that cinema therapy is effective in increasing the empathy of tarbiyah students of UIN Raden Fatah.